How has COVID-19 pandemic changed flu vaccination attitudes among an Italian cancer center healthcare workers? - Lucia Bertoni; Andrea Roncadori; Nicola Gentili; Valentina Danesi; Ilaria Massa; Oriana Nanni; Mattia Altini; Giovanni Gabutti; Maria Teresa Montella (Taylor & Francis Group, 2022)
A retrospective study was conducted among Italian cancer healthcare workers (HCWs) to describe how influenza vaccination attitudes have changed during the COVID-19 pandemic. The analysis was conducted on the last three influenza seasons (2018/19, 2019/20 and 2020/21). To account for different relationships and proximity with patients, the study population was grouped into three main professional categories: health personnel, administrative staff and technicians. Moreover, to explore the factors affecting the coverage of influenza vaccine, a multinomial regression analysis was performed.Over the years, the influenza vaccination uptake showed a gradual increase across the overall staff, the highest coverage (53.8%) was observed in the season 2020/21, in particular, for health personnel (57.7%). In general, males resulted in more adherent to vaccination campaigns; nevertheless, this gap decreased in the last season. A total of 28.6% workers were always vaccinated throughout the past three seasons, a remarkable 25.2% (mainly young and females) received for the first time the influenza vaccination in 2020/21.In this dramatic health crisis, the attitudes of HCWs toward flu vaccination have changed. The COVID-19 outbreak increased adherence to flu vaccination, reaching the highest coverage in the campaign 2020/21. However, further efforts should be made to achieve greater vaccination coverage.